Seed Priming Improves the Germination Traits of Tall Fescue (Festuca arundinacea) - Hossein Reza ROUHI (Notulae Scientia Biologicae, 2011)
A couple of experiments were carried out to investigate the effects of osmopriming and hydropriming treatments on the germination indexes and seed vigor of Tall fescue (Festuca arundinacea). In the first experiment, fulfilled based on randomized complete block designed with four replicates, the effect of polyethyleneglycol 6000 solution with five osmotic potentials (-8, -10, -12, -14 and -16 bar), two temperatures (15 and 25oC) and four time intervals (12, 24, 36 and 48 hours) was analized. The second experiment was fulfilled by using distilled water at two temperatures (15 and 25oC) and four time intervals (12, 24, 36 and 48 hours) with four replicates on the above mentioned data. Then, based on the maximum germination rate and vigor indexes, the optimal treatment composition was determined for osmopriming and hydropriming solutions in regard to the osmotic potential, temperature and priming duration. In osmopriming experiment, treatment composition of 12 hours at 15oC and -8 bar had the most significant effect on the percent and speed of germination, length of radicle, coleoptile and seedling, as well as vigor indexes in Tall fescue. For hydropriming, the effect analyzed in the same condition as osmopriming, was observed in the majority of evaluated traits; treatment composition of 12 hours prime and 15oC had the maximum numerical value in comparison to control and other treatments. Finally, it is inferred that favorable effects of osmo- and hydropriming at 15oC temperature are more significant in comparison with the control group (none prime seeds).